The influence of moisture on the energy performance of retrofitted walls - Vasco Peixoto de Freitas (2020)
. The renovation of old building facades should be performed mainly considering the building energy demand reduction. For this purpose, it is necessary to select retrofitted solutions that should be able of minimizing heat losses through walls. However, it is not only the nominal thermal transmittance that influences the amount of heat transported through the wall, but also the moisture content within the walls under inservice conditions. The main objective of this paper is the evaluation of the influence of the moisture content on the energy performance of retrofitted walls. A numerical study using the software WUFI Pro was carried out to quantify the influence of wind driven rain on the thermal transmittance of different wall assemblies exposed to different climates and orientations. This study reports the transient thermal transmittance of different retrofitted wall solutions as a function of moisture content.